2021
DOI: 10.1177/15353702211053588
|View full text |Cite
|
Sign up to set email alerts
|

Identifying immune subtypes of uterine corpus endometrial carcinoma and a four-paired-lncRNA signature with immune-related lncRNAs

Abstract: Uterine corpus endometrial carcinoma (UCEC) is the third most frequent gynecological malignancies in the female reproductive system. Long non-coding RNAs (lncRNAs) are closely involved in tumor progression. This study aimed to develop an immune subtyping system and a prognostic model based on lncRNAs for UCEC. Paired lncRNAs and non-negative matrix factorization were applied to identify immune subtypes. Enrichment analysis was conducted to assess functional pathways, immune-related genes, and cells. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
3
2
0
Order By: Relevance
“…A high-risk group may be more sensitive to PD – 1/L1 immunotherapy and JNK inhibitors VIII, Z.LLNle.CHO, DMOG. The four immune-related lncRNAs were extremely effective in the overall OS prognosis of UCEC, which was similar to our study design ( 32 ). It was nevertheless possible for them to distinguish patients from different UCECs despite the NMF algorithm they employed to classify the population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A high-risk group may be more sensitive to PD – 1/L1 immunotherapy and JNK inhibitors VIII, Z.LLNle.CHO, DMOG. The four immune-related lncRNAs were extremely effective in the overall OS prognosis of UCEC, which was similar to our study design ( 32 ). It was nevertheless possible for them to distinguish patients from different UCECs despite the NMF algorithm they employed to classify the population.…”
Section: Discussionsupporting
confidence: 86%
“…GSEA showed that cell cycle, fc gamma r mediated phagocytosis, Nod like receptor signaling pathway, pathways in cancer, oocyte meiosis, progesterone mediated oocyte maturation, ubiquitin mediated proteolysis, Notch signaling pathway, JAK-STAT signaling pathway, erbb signaling pathway were mainly enriched in the high-risk group. PHE The four immune-related lncRNAs were extremely effective in the overall OS prognosis of UCEC, which was similar to our study design (32). It was nevertheless possible for them to distinguish patients from different UCECs despite the NMF algorithm they employed to classify the population.…”
Section: Discussionsupporting
confidence: 80%
“…These findings not only support the results of this study, but further support ongoing research demonstrating GZMK's role in breast cancer progression. Similarly, GZMB mutations in GBM and PRF1 mutations in colorectal cancer and UCEC align with literature suggesting the impact of these genes on patient survival in specific cancer types [56][57][58][59][60].…”
Section: Discussionsupporting
confidence: 81%
“…LncRNAs have regulatory functions [29,30]. They participate in epigenetic regulation, maintain chromatin structure, and modulate transcription [30,31].…”
Section: Discussionmentioning
confidence: 99%